PENYIMPANAN DINGIN SAYUR SAWI HIJAU (BRASSICA JUNCEA L) MENGGUNAKAN KOTAK PENDINGIN SEDERHANA - Senia Ubis; Handry Rawung; Stella M.E. Kairupan; Hildy Wullur (Universitas Sam Ratulangi, 2015)
ABSTRACTThis study aims to modify the cold storage tool for green cabbage, assessing air circulation by measuring the temperature in the ice chamber, chamber vegetables, vegetable base, stem and leaf vegetables, vegetables weight loss measure, calculate the cooling rate is based on temperature measurements, measure the storage time with a freshness indicator and measure humidity outside environment, this study uses descriptive method. Temperature measurement starts with measuring the temperature of the ice which is used as a coolant in the cooling box is simple. After being measured and the measurement data obtained after the average is taken of the obtained temperature of ice -20áµ’C. 6 From the graph it appears that at the beginning of the cold storage temperature drops drastically visible in all sections where the thermometer is installed. The fall in temperature is due to the sublimation process that begins with the process of convection heat transfer between the air in the ice room with a block of ice. When traced line temperature curve for all observation points per day then obtained an average temperature of space vegetables and vegetables are in a position under 10áµ’C from the first day until the day of the fifth and sixth while the ice room temperature is under 10áµ’C only until the day to five. For day to six, seven and eight all temperatures have been in the position above 10áµ’C. Weight loss data observed or measured at the beginning and end of the cold storage. The difference between the initial weight of the final weight or lose weight, as in the figure averaged 57.3 gr. The cooling rate is a function of temperature fluctuations within a certain time or depending on the initial temperature and the temperature of a particular moment. In this study, the initial temperature and the temperature at certain times fluctuate so that the calculations, the positive numbers and a minus. The highest cooling rate was obtained at room temperature ice is 0,64áµ’C / h and the lowest cooling rate was obtained at room temperature ice also is -0.39áµ’C / h. The results of visual observation is also in accordance with the temperature graph obtained, wherein the vegetable room temperature begins to rise beyond 10áµ’C after the fifth day of the storage process in progress. Thus it can be said that the duration of cold storage greens using a simple cooler box can only last for five days of storage. Measurement of moisture was observed only on the outside or environmental humidity and wet bulb thermometer observed in the dry and the ball is then plotted on a graph psychrometric chart. Graph of Figure 11 above shows that the humidity during the day at 01.00pm low humidity and late afternoons outside air humidity tends to increase and reached a peak in the morning at 04.00 amKeywords : cold storage, cabbage, box cooler